EVALUATING THE USER EXPERIENCE IMPACT OF VIRTUAL REALITY ON CULTURAL HERITAGE: A UEQ-BASED APPROACH - Indra Iswara, Ida Bagus Ary; Laksana, Made Satyadharma (Proceeding International Conference on Information Technology, Multimedia, Architecture, Design, and E-Business, 2024)
The Penataran Sasih Temple Virtual Reality Tour website is a website that contains various metadata on the Penataran Sasih Temple digitally which aims to digitally preserve and inventory all the metadata contained in the Penataran Sasih Temple. In this research, we want to know the comfort level of users in terms of User Experience in using the Pura Penataran Sasih Virtual Reality Tour Website. So in this research an evaluation of the user experience of the Virtual Reality Tour Website was carried out. Evaluation was carried out using the User Experience Questionnaire (UEQ) method. User Experience Questionnaire (UEQ) is a type of questionnaire that is able to provide an overview of aspects of usefulness and user experience. Evaluation results The mean or average of the 6 test variables, starting from the attractiveness scale, reached an average of 2.21. clarity 2.09, efficiency 2.14, accuracy scale 2.02, stimulation scale 2.26 and novelty 1.97. The benchmark results show that the average of the existing scale is in the excellent (very good) category. This research is expected to provide better insights into the user experience, as well as recommendations for continuous improvement on these digital platforms.